2015
DOI: 10.1016/j.paid.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

The Big Five personality traits as antecedents of eco-friendly tourist behavior

Abstract: a b s t r a c tThis article reports the findings of a study, conducted among 227 foreign tourists who visited Cyprus, that aimed to identify the relationships between the Big Five personality dimensions and tourists' environmentalism. Structural equation modeling revealed that Agreeableness, Conscientiousness, Extraversion, and Neuroticism are positively associated with pro-environmental tourist behavior. In contrast, no significant relationship was observed between Openness and ecological action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
146
6
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(172 citation statements)
references
References 32 publications
11
146
6
9
Order By: Relevance
“…Neuroticism positively influences external locus of control [30,31]. [30,31], and positively influences proenvironmental behavior [43,52,59]. The second model assumes, therefore, external locus of control positively influences pro-environmental behavior.…”
Section: H1 Emotional Stability Positively Influences Internal Locusmentioning
confidence: 99%
“…Neuroticism positively influences external locus of control [30,31]. [30,31], and positively influences proenvironmental behavior [43,52,59]. The second model assumes, therefore, external locus of control positively influences pro-environmental behavior.…”
Section: H1 Emotional Stability Positively Influences Internal Locusmentioning
confidence: 99%
“…Research in social psychology has shown that personality traits often determine an individual's beliefs and behavior across different aspects of life (Digman, 1990). Studies have tested the role of personality in a variety of contexts, like behavior in trading activities (Kleine, Wagner, & Weller, 2015), eco-friendly behavior (Fraj & Martinez, 2006;Kvasova, 2015), social networks use (see e.g., Amichai-Hamburger & Vinitzky, 2010;Hughes, Rowe, Batey, & Lee, 2012;Kokkinos, Baltzidis, & Xynogala, 2016).…”
Section: Personality Traitsmentioning
confidence: 99%
“…Research on the ecological behavior of consumers, and specifically in the field of tourism, is scarce in terms of knowledge of the importance of psychosocial factors, attitudes, or sociocultural factors (Weaver and Lawton 2007, do Paço and Raposo 2009, Han 2015, Hultman et al 2015, Kvasova 2015, Kiatkawsin and Han 2017. Furthermore, the literature review emphasizes the need to deepen the understanding of environmentally responsible behavior by incorporating the external, contextual, or group variables that influence such behavior (Miguens et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the literature review emphasizes the need to deepen the understanding of environmentally responsible behavior by incorporating the external, contextual, or group variables that influence such behavior (Miguens et al 2015). In addition, scant research exists on the relationship between personality traits and the environmentally responsible behavior of individuals in the tourism industry (Kvasova 2015). It is important to remember that ecotourists are a type of consumer with their own characteristics; they are interested in environmental conservation and the cultural preservation of the places they visit as well as experiencing and learning new things from the natural environment (Juric et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation